Dictionary of the history of ideas studies of selected pivotal ideas - Wiener, Philip P. (Philip Paul) 1905-1992. (New York Scribner, 1973)
Contains overviews of religious, intellectual, literary, economic, political, and scientific concepts.
v. 1. Abstraction in the formulation of concepts, to Design argument -- v. 2. Despotism, to Law, common -- v. 3. Law, conception of, to Protest movements -- v. 4. Psychological ideas, to Zeitgeist -- [5] Index.
Includes bibliographical references.
Also issued online.
Keywords: Civilization -- History -- Dictionaries; Intellectual life -- History -- Dictionaries